2020
DOI: 10.1093/ajcp/aqaa108
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Examination Findings in SARS-CoV-2 Infection

Abstract: Abstract Objectives Peripheral blood abnormalities in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have not been fully elucidated. We report qualitative and quantitative peripheral blood findings in coronavirus disease 2019 (COVID-19) patients and compare them with a control group. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 25 publications
5
74
0
8
Order By: Relevance
“…However, we noticed another nuclear change in neutrophils in the form of Howell-Jolly body-like inclusions that was seen in 10% of patients with COVID-19. Similar to our findings, Nazarullah et al 6 have reported the presence of neutrophil toxic granulation and myeloid left shift, as well as the increased frequency of plasmacytoid lymphocytes in COVID-19–positive patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, we noticed another nuclear change in neutrophils in the form of Howell-Jolly body-like inclusions that was seen in 10% of patients with COVID-19. Similar to our findings, Nazarullah et al 6 have reported the presence of neutrophil toxic granulation and myeloid left shift, as well as the increased frequency of plasmacytoid lymphocytes in COVID-19–positive patients.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, despite a clearly significant role that monocytes/macrophages play in sustaining a hyperinflammatory response in SARS-CoV-2 infection, it appears that not all patients with COVID-19 display monocyte morphologic changes in peripheral blood that we describe in our study. Nazarullah et al 6 have reported quantitative and qualitative peripheral blood changes in 12 COVID-19–positive patients and found that in their cohort, the most significant morphologic changes were related to nuclear morphology in neutrophils showing acquired Pelger-Huët anomaly and monolobate neutrophils. While we did find similar nuclear changes, they were present in a small number of neutrophils (predominantly <5% of neutrophils) and were not specific to COVID-19–positive patients; similar findings were present in COVID-19–negative ICU patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They showed that the pseudo-Pelger-Huet anomaly was recorded in all cases of COVID-19, affecting more than 5% of granulocytes in most cases. 21 Yunus Murat Akcabelen et al reported dysplastic changes in peripheral blood cells of COVID-19 patients. We also observed atypical lymphocytes, pseudo-Pelger-Huet anomaly, and dysplastic changes in peripheral blood cells in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to SARS-CoV and MERS-CoV, older age is a risk factor for severe SARS-CoV-2. Whereas absolute lymphopenia is not specific to COVID-19, low CD3+, CD4+, and CD8+ T cell counts in peripheral blood have been observed in severe cases of COVID-19[39]. These cases also -21 -present with comorbidities such as chronic underlying diseases.…”
mentioning
confidence: 99%